Evaluación de la viabilidad técnico-financiera de la producción de abono orgánico mediante el compostaje para el manejo adecuado de los residuos sólidos en el municipio de Puerto Gaitán, Meta (2019)
The objective of this project is to generate a proposal for the use of organic organic waste in the middle of the production of organic fertilizer through composition in the municipality of Puerto Gaitán, Meta. As a first instance, a diagnosis of solid waste generated in the municipality was made, taking into account as a basis the information presented in the PGIRS. Subsequently, the main types of composition that are currently used are compared, reaching the conclusion that the procedure is more feasible and efficient, is vermicomposting. Following this, it was proposed to perform a sampling technique with the objective of knowing in how many places the collection of the RSOs would be made. Additionally, a socialization strategy was implemented in the municipality regarding the management of organic waste, in order to facilitate the collection of these. For the diagnosis of this project, a random collection was carried out in some homes in the urban sector of the municipality, where a total of 17 kg of solid organic waste was obtained. Subsequently, a sample of the collected waste was taken for its characterization, in order to adjust the most influential physicochemical parameters, and in this way to be able to start the vermicomposting process. According to the above, it was proposed to adjust the Carbon / Nitrogen ratio, being the most influential parameter in the quality of the organic fertilizer.